PERAN AYAH DALAM MEMBANGUN KESEHATAN MENTAL KELUARGA PADA MAHASISWA PENDIDIKAN SOSIOLOGI ANGKATAN 2022 UNIVERSITAS SULTAN AGENG TIRTAYASA - Christin Yulina; Septi Kuntari (Yayasan Literasi Sains Indonesia, 2025)
This study aims to explore the role of fathers in supporting the mental health of Sociology Education students from the 2022 cohort at Sultan Ageng Tirtayasa University. Using a qualitative phenomenological approach, this research delves into students’ subjective experiences regarding the emotional and psychological support provided by their fathers. The main focus is to examine how a father's presence, communication, and involvement contribute to students' mental stability in facing academic and social pressures within the university environment. The findings reveal that students who have a close and communicative relationship with their fathers tend to possess higher self-confidence, emotional stability, and stronger adaptive abilities. Conversely, the absence or lack of emotional involvement from fathers can lead to anxiety, loneliness, and even social withdrawal. These findings emphasize that a father's role is not limited to fulfilling material needs but also as an emotional support figure who plays a vital role in shaping psychological resilience in children, especially during the transitional phase into adulthood and independence.